Robots with human intelligence. (Futurist)
According to Hans Moravec, director of Carnegie Mellon University's Mobile Robot Laboratory and author of the book Mind Children: The Future of Robot and Human Intelligence, robots with the equivalent of human intelligence will be common within 50 years. Artificial-intelligence researchers now find it fairly easy to give computers adult-level performance skills for solving problems on intelligence tests or for playing games. Increasing the machines' perceptual and motor skills is the next hurdle. In an imitation of the process by which animal minds evolve, researchers are adding perceptual and motor qualities to machines a few at a time to make the resulting sequence of machine behaviors resemble the capabilities of animals with increasingly complex nervous systems. Moravec estimates that the advent of fully intelligent machines will occur in about 40 years.